رؤية شاملة لمكافحة ظاهرة الاتجار بالبشر في العراق بعد عام 2003 - نشمى، سعد جمار; عباس، أمين ياسين (الجامعة الأردنية - عمادة البحث العلمي, 2020)
اتخذ العراق استراتيجيات عديدة لمكافحة ظاهرة الاتجار بالبشر، إلا أنها لم تكن بالمستوى المطلوب فقد ثبت عجزها في مكافحتها، نظرا لغياب رؤية وطنية فاعلة في ظل قدرة العصابات المنظمة على استحداث أساليب لتنفيذ عمليات الاتجار، وساعد في تنامي هذه الظاهرة وجود عوامل اقتصادية أو اجتماعية أو سياسية، فضلا عن ظروف الحرب التي ألمت بالعراق المتمثلة بالاحتلال الأمريكي وما أعقبه من انفلات أمني، ومما زاد الأمر سوءاً الآثار السلبية التي خلفها تنظيم داعش على المجتمع العراقي بعد سيطرته على ارضي واسعة من العراق، وقد شكلت هذه العوامل تربة خصبة للعصابات المنظمة لتوسيع أنشطتها المتعلقة بالاتجار. وعليه اقتضي بحثنا طرح رؤية متكاملة لغرض تقليل معدلاتها، ومن ثم الوصول إلى القضاء عليها من خلال الوقوف على الاستراتيجية الحالية التي تتبعها الحكومة العراقية لبيان أوجه القصور الذي يعتريها واقتراح المعالجة
Iraq has taken many strategies to combat trafficking phenomenon, but it was not to required level has proved unable to combat the absence of an effective national vision in the light of ability of organized gangs to develop methods to carry out trafficking operations and helped in the escalations of the phenomenon of economic, social or political factors as well as the conditions of was that plagued Iraq represented by USA occupations and the ensuring insecurity which was worse by the negative effects of ISIS on Iraq society after its control over a large territory. These factors have provided fertile organized gangs to expand its activities related to trafficking according. Our research required to put forward an integrated vision for purpose for reducing their rates and then reach to eliminate them by identifying current strategy adopted by the Iraqi government to indicate the short coming and suggest a treatment.
Keywords: جريمة الاتجار بالبشر -- الجريمة المنظمة -- مكافحة الجريمة -- العراق